Comparative expression profiling reveals gene functions in female meiosis and gametophyte development in Arabidopsis. (30th September 2014) - Zhao, Lihua; He, Jiangman; Cai, Hanyang; Lin, Haiyan; Li, Yanqiang; Liu, Renyi; Yang, Zhenbiao; Qin, Yuan
Summary Megasporogenesis is essential for female fertility, and requires the accomplishment of meiosis and the formation of functional megaspores. The inaccessibility and low abundance of female meiocytes make it particularly difficult to elucidate the molecular basis underlying megasporogenesis. We used high‐throughput tag‐sequencing analysis to identify genes expressed in female meiocytes (FMs) by comparing gene expression profiles from wild‐type ovules undergoing megasporogenesis with those from the spl mutant ovules, which lack megasporogenesis. A total of 862 genes were identified as FMs, with levels that are consistently reduced in spl ovules in two biological replicates. Fluorescence‐assisted cell sorting followed by RNA‐seq analysis of DMC1:GFP‐labeled female meiocytes confirmed that 90% of the FMs are indeed detected in the female meiocyte protoplast profiling. We performed reverse genetic analysis of 120 candidate genes and identified four FM genes with a function in female meiosis progression in Arabidopsis. We further revealed that KLU, a putative cytochrome P450 monooxygenase, is involved in chromosome pairing during female meiosis, most likely by affecting the normal expression pattern of DMC1 in ovules during female meiosis. Our studies provide valuable information for functional genomic analyses of plant germline development as well as insights into meiosis.